Heart rate variability characteristics of patients with irritable bowel syndrome and associations with symptoms. Issue 7 (25th March 2018) - Polster, A.; Friberg, P.; Gunterberg, V.; Öhman, L.; Le Nevé, B.; Törnblom, H.; Cvijovic, M.; Simren, M.
Abstract: Background: Disturbed brain‐gut interactions are assumed to be of importance for symptom generation in patients with irritable bowel syndrome (IBS). The autonomic nervous system (ANS) is part of the bidirectional brain‐gut communication, but previous studies in IBS show diverging results. We aimed to identify subgroups of IBS patients with distinct ANS characteristics differentiating them from healthy controls (HC), and to study associations between ANS status and symptoms. Methods: Heart rate variability (HRV) was measured in IBS patients and HC (Holter monitoring: supine and standing positions with controlled respiration and ambulatory 24‐hour period). Frequency (5 minutes, supine, standing) and time domains (24 hours, day, night) were analyzed. Validated questionnaires were used to measure gastrointestinal and psychological symptoms in patients. Patients and HC were compared on a univariate and multivariate level (principal component analysis [PCA] and orthogonal partial least squares discriminatory analysis (OPLS‐DA)). Key Results: We analyzed 158 IBS patients (Rome III) and 39 HC. Patients differed significantly from HC in HRV parameters during daytime and in standing position. In the PCA, a majority of patients overlapped with HC, but the weighted means differed ( P  < .01). A subset of patients (n = 30; 19%) with an aberrant global HRV profile was identified through PCA and OPLS‐DA; these patients reported more severe symptoms of frequent ( P  < .05) and loose stools ( P  = .03), as well as urgency ( P  = .01). Conclusions and Inferences: Altered ANS function was demonstrated in patients with IBS, and this might be of particular relevance for symptoms in a subset of the patients. Abstract : A dysfunction of brain‐gut communication is assumed to be of key importance for irritable bowel syndrome (IBS) etiology, but the role of the autonomic nervous system (ANS) in symptom generation in IBS is poorly understood. This study shows that heart rate variability (HRV), a proxy measure for overall ANS function, differs significantly between IBS patients and healthy controls when the ANS is challenged (daytime measures and orthostatic stress), as well as on a multivariate level. A subgroup of IBS patients (19%) showed an altered global HRV profile, which distinguished them from other IBS patients and healthy controls. This subgroup reported more severe diarrhea. Our findings indicate that altered ANS function might be of relevance for symptoms in a subset of patients with IBS.